Comprehensive pan-cancer analysis indicates key gene of p53-independent apoptosis is a novel biomarker for clinical application and chemotherapy in colorectal cancer - Yan, Jianing; Wang, Jingzhi; Miao, Min; Shao, Yongfu (Frontiers in Immunology, 2025)
BackgroundSchlafen11 (SLFN11) is a key gene in p53-independent apoptosis through ribosome stalling; however, systematic research has been conducted on its role in the tumor immune microenvironment, clinical application, and immunotherapy response across pan-cancer.MethodPublic data were downloaded and multi-omics approaches were used to investigate the relationship between the expression level of SLFN11 and spatial position, biological function, immune landscape, and clinical application values. Cell Counting Kit-8 assay and quantitative real-time PCR were used to validate the expression level of SLFN11 and drug sensitivity in colorectal cancer samples.ResultOur study revealed that SLFN11 was downregulated in most cancers and correlated with DNA repair, the P53 pathway and immune response in tumor development progress by multi-omics analysis. Dysregulated SLFN11 is accompanied by several immune cell infiltrations and immune-related regulators, which can be a promising screening and prognostic biomarker and chemotherapy predictive target for clinical application. In vitro experiments proved that downregulated SLFN11 is a useful diagnostic biomarker and is linked to imatinib resistance in colorectal cancer.ConclusionThe expression level of SLFN11 has a substantial promise as a valuable biomarker for diagnosis and a predictive indicator for assessing the effectiveness of chemotherapy and immunotherapy in human cancers, which deserves further additional basic experiments and clinical trials to prove.